Altered Gut Microbiota and Short-Chain Fatty Acids After Vonoprazan-Amoxicillin Dual Therapy for Helicobacter pylori Eradication - Hu, Yi; Xu, Xin; Ouyang, Yao-Bin; He, Cong; Li, Nian-Shuang; Xie, Chuan; Peng, Chao; Zhu, Zhen-Hua; Shu, Xu; Xie, Yong; Lu, Nong-Hua; Zhu, Yin (Frontiers in Cellular and Infection Microbiology, 2022)
The combination of vonoprazan (VPZ) and amoxicillin (VA therapy) has been shown to achieve acceptable eradication rates for Helicobacter pylori (H. pylori). Herein, our aim was to explore the short-term effect of VA therapy on the gut microbiota and short-chain fatty acids (SCFAs) using human fecal samples. A total of 119 H. pylori-positive patients were randomized into low- or high-dose VA therapy (i.e., amoxicillin 1 g b.i.d. or t.i.d. and VPZ 20 mg b.i.d.) for 7 or 10 days. Thirteen H. pylori-negative patients served as controls. Fecal samples were collected from H. pylori-positive and H. pylori-negative patients. The gut microbiota and SCFAs were analyzed using 16S rRNA gene sequencing and gas chromatography–mass spectrometry, respectively. The gut microbiota in H. pylori-positive patients exhibited increased richness, diversity and better evenness than matched patients. Fifty-three patients studied before and after H. pylori eradication were divided into low (L-VA) and high dose (H-VA) amoxicillin dose groups. The diversity and composition of the gut microbiota among L-VA patients exhibited no differences at the three time points. However, among H-VA patients, diversity was decreased, and the microbial composition was altered immediately after H-VA eradication but was restored by the confirmation time point. The decreased abundance of Anaerostipes, Dialister and Lachnospira induced by H-VA was associated with altered SCFAs levels. VA dual therapy for H. pylori eradication has minimal negative effects on gut microbiota and SCFAs.